2000
DOI: 10.1161/01.str.31.10.2314
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Autoregulation in Subjects Adapted and Not Adapted to High Altitude

Abstract: Background and Purpose-Impaired cerebral autoregulation (CA) from high-altitude hypoxia may cause high-altitude cerebral edema in newcomers to a higher altitude. Furthermore, it is assumed that high-altitude natives have preserved CA. However, cerebral autoregulation has not been studied at altitude. Methods-We studied CA in 10 subjects at sea level and in 9 Sherpas and 10 newcomers at an altitude of 4243 m by evaluating the effect of an increase of mean arterial blood pressure (MABP) with phenylephrine infusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
66
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 35 publications
7
66
4
Order By: Relevance
“…The 22% lower MCAv in the HA natives compared with lowlanders in the present study is also different than this previous report, 15 where comparable MCAv was reported (Sherpa: 61 ± 11; lowlanders: 63±12 cm/second). Early studies have established that natives with chronic mountain sickness and related polycythemia have reductions in CBF compared with chronic mountain sickness-free natives and lowlanders (e.g.…”
Section: Methodological Considerationscontrasting
confidence: 99%
See 4 more Smart Citations
“…The 22% lower MCAv in the HA natives compared with lowlanders in the present study is also different than this previous report, 15 where comparable MCAv was reported (Sherpa: 61 ± 11; lowlanders: 63±12 cm/second). Early studies have established that natives with chronic mountain sickness and related polycythemia have reductions in CBF compared with chronic mountain sickness-free natives and lowlanders (e.g.…”
Section: Methodological Considerationscontrasting
confidence: 99%
“…Findings showed that HA Sherpa, and most lowlanders arriving to HA, had impaired cerebral pressure-flow responses at 4,243 m, as reflected in a more pressure-passive response to acute hypertension compared with a sea-level (SL) group in their cross-sectional study. 15 In their follow-up study, 16 it was reported that Sherpa who resided below 4,000 m had an intact pressure-flow response; however, in those residing above 4,000 m, the chronic exposure to hypoxia led to more pressure-passive responses, indicative of impaired cerebral autoregulation. 16 In addition, the impairment in steady-state (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations